The feature and significance of lower limb MRI in adult myositis patients with anti-NXP2 antibody: a retrospective cohort study in China - Shanshan, Li; Lu, Wang; Chao, Sun; Ling, Zhang; Jianghui, Duan; Jianyu, Zhu (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to describe the MRI features of lower limbs (thighs and calves) in patients with anti-NXP2 antibody positive myositis, and explore their relationship with clinical manifestations and prognosis.MethodsAdult patients with anti-NXP2 antibody who underwent both thigh and calf MRI examinations simultaneously were enrolled between 2017 and 2023. The MRI features and medical records of patients were reviewed. Statistical analysis was conducted by SPSS 21.0.ResultsA total of 48 patients (29 females and 19 males) were included in the study. There were fifteen and seven patients with subcutaneous edema on the thigh and calf MRI, respectively. The incidence of fascia edema in the thigh was higher than that in the calf (50.0% vs. 22.9%, p = 0.006). All patients experienced varying degrees of thigh muscle edema, with 41 cases (85.4%) showing calf muscle edema on MRI. The primarily affected group in the thigh was the anterior muscle, while the anterior and posterior groups of the calf were equally affected. In addition, the inflammation score of muscle MRI was positively correlated with disease activity (r = 0.316, p = 0.029), the level of muscle enzymes, serum ferritin (r = 0.439, p = 0.002), D-dimer (r = 0.410, p = 0.004), and NSE (r = 0.420, p = 0.006). Patients with diffuse pattern on MRI generally exhibited higher disease activity. However, there was no difference in the frequency of relapse and mortality between patients with and without diffuse lesions on MRI.ConclusionLower limb MRI of patients with anti-NXP2 antibody provided useful information in evaluating the extent and distribution of lesions. In addition, the degree of muscle edema on MRI was significantly correlated with various clinical features.